Strategi Mempertahankan Hubungan Pertemanan Lawan Jenis pada Dewasa Muda - Safira Tiara Dewi; Wenty Marina Minza (Faculty of Psychology, Universitas Gadjah Mada, 2016)
Cross-sex friendship is often regarded as a romantic relationship. The lack ofsocial norms that managed these relationships in society makes the individuals dealingwith the challenge of maintaining relationships. Young adults become one of thecategories that face this challenge because at this time the relationship between men andwomen is more prominent than the other phases. Based on his romantic intentions, cross-sex friendship is divided into four types, strictly platonic, mutual romance, rejectsromance, and desires romance. This research was conducted to find out the challengesfaced in cross-sex friendship and strategy to maintain the relationship. This research usesqualitative method with phenomenology approach. Methods of data collection used inthis study are semi-structured interviews and observation. The study's informantsconsisted of four people or two pairs of young adults who are in cross-sex friendship.Research shows that individual differences in seeing the friendship of the opposite sexcause different challenges and strategies to maintain cross-sex friendships.